STRATEGI KOMUNIKASI DINAS PARIWISATA KOTA BOGOR DALAM MEMBANGUN CITRA DESTINASI WISATA HALAL - Widia Pawesti, Khoiriah (EDUTECH CONSULTANT, 2019)
This research was conducted with the aim to find out how the communication strategy of the City of Bogor Tourism Office in building the image of halal tourist destinations. This study used qualitative research methods. The population in this study is the Bogor City Tourism Office. In this study using SWOT analysis to determine the internal and external of a company. The results showed that the Department of Tourism used SO strategy, one of which was to increase cooperation between halal tourism managers and the Bogor Tourism Office related to developing halal tourism.